2020
DOI: 10.4102/ajod.v9i0.618
|View full text |Cite
|
Sign up to set email alerts
|

Functional outcome of stroke inpatients according to human immunodeficiency virus status: A feasibility study

Abstract: This feasibility study aims to determine the requirements for a large descriptive cohort, to adequately describe the functional outcome of stroke patients with varying HIV status.Method: All stroke patients meeting the inclusion criteria were recruited over a 6-month period at a South African inpatient rehabilitation centre. Data were collected on admission and discharge using outcome measures including the Barthel Index (BI), Berg Balance Scale (BBS) and the use of assistive devices used to describe independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…The Katz Index of Activities of Daily Living (Katz ADL) is another commonly used measure for assessing disability and functional status post-injury [18,19]. While the Katz ADL has been used primarily in geriatric and chronically ill patient populations to evaluate functional capacity to independently perform activities typical in daily life, it has not been commonly studied among younger patient populations and those recovering from acute trauma [20][21][22][23]. One previous study comparing postoperative disability among surgical patients found correlation between the Katz ADL and WHODAS 2.0, suggesting that either could be useful in characterizing the functional status in such populations [24].…”
Section: Introductionmentioning
confidence: 99%
“…The Katz Index of Activities of Daily Living (Katz ADL) is another commonly used measure for assessing disability and functional status post-injury [18,19]. While the Katz ADL has been used primarily in geriatric and chronically ill patient populations to evaluate functional capacity to independently perform activities typical in daily life, it has not been commonly studied among younger patient populations and those recovering from acute trauma [20][21][22][23]. One previous study comparing postoperative disability among surgical patients found correlation between the Katz ADL and WHODAS 2.0, suggesting that either could be useful in characterizing the functional status in such populations [24].…”
Section: Introductionmentioning
confidence: 99%